2011
DOI: 10.1371/journal.pone.0014793
|View full text |Cite
|
Sign up to set email alerts
|

Down-Regulation of the Canonical Wnt β-Catenin Pathway in the Airway Epithelium of Healthy Smokers and Smokers with COPD

Abstract: BackgroundThe Wnt pathway mediates differentiation of epithelial tissues; depending on the tissue types, Wnt can either drive or inhibit the differentiation process. We hypothesized that key genes in the Wnt pathway are suppressed in the human airway epithelium under the stress of cigarette smoking, a stress associated with dysregulation of the epithelial differentiated state.Methodology/Principal FindingsMicroarrays were used to assess the expression of Wnt-related genes in the small airway epithelium (SAE) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
80
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(94 citation statements)
references
References 73 publications
12
80
2
Order By: Relevance
“…Although Heijink et al found that CSE decreased WNT4 and other WNT components in 16HBECs, 30 they did not study the potential role of the decreased WNT pathway in CS-related airway inflammation. Interestingly, it has been found that the mRNA levels of β-catenin were downregulated in the primary airway epithelium of smokers and smokers with COPD 13 and the number of β-catenin-positive staining alveolar epithelial cells were decreased in COPD patients compared with controls. 12 These studies suggested a crucial role of the WNT/β-catenin signaling in airway differentiation and alveolar tissue repair in COPD respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although Heijink et al found that CSE decreased WNT4 and other WNT components in 16HBECs, 30 they did not study the potential role of the decreased WNT pathway in CS-related airway inflammation. Interestingly, it has been found that the mRNA levels of β-catenin were downregulated in the primary airway epithelium of smokers and smokers with COPD 13 and the number of β-catenin-positive staining alveolar epithelial cells were decreased in COPD patients compared with controls. 12 These studies suggested a crucial role of the WNT/β-catenin signaling in airway differentiation and alveolar tissue repair in COPD respectively.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Recently, WNT/β-catenin signaling has been implicated in tissue injury and the regeneration of COPD. [12][13][14] The activity of WNT/β-catenin signaling was decreased in the alveolar epithelial type II (ATII) cells of COPD patients and an emphysema mice model. 12 Wang et al 13 found that the expression profile of WNT/β-catenin signaling was decreased in the small airway epithelium of COPD patients and smokers, suggesting its important role in airway epithelium differentiation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the present study is in line with these reports, confirming that aberrant activation of Wnt/β-catenin signaling exists in cigarette smoke-associated airway injury and is responsible for cell proliferation and tissue remodeling at the late stage of injury in response to CSE stimuli. However, one report has contradicted these studies, suggesting that smoking downregulates the Wnt/β-catenin pathway in the human airway epithelium and contributes to the dysregulation of airway epithelium differentiation observed in smoking-related airway disorders (24).…”
Section: Discussionmentioning
confidence: 99%
“…The Wnt pathway has been associated with normal lung development and homeostasis as well as chronic lung diseases such as fibrosis and asthma (Konigshoff et al, 2010;Van et al, 2008). However, there are contradictory findings indicating that the Wnt pathway is activated or down-regulated by cigarette smoke in bronchial epithelial cells (Lemjabbar-Alaoui et al, 2006;Wang et al, 2011). Wnt inhibitory factor 1 (Wif1), an extracellular antagonist that acts by binding to Wnt ligands, is a frequent target for epigenetic silencing in various human cancers (Ying et al, 2009).…”
Section: Introductionmentioning
confidence: 99%